Sustainable Weed Management - Restuccia, Alessia; Scavo, Aurelio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Weeds are the most important biological factor that affects yield in herbaceous and perennial crops. Nowadays, following the recommendations of government institutions and public opinion, there is an urgent need to search for sustainable weed management practices that have a low impact on the environment and on the health of living organisms. This reprint, established after closing the Special Issue "Sustainable Weed Management" edited by Dr. Alessia Restuccia and Dr. Aurelio Scavo, is a collection of papers (17 research articles and 1 review) related to the recent advancements in sustainable weed control methods and to the biotic and abiotic factors affecting weed adaptation.